The determination of the crystal structure of four compounds of industrial importance - Banerjee, Anuradha (1985)
This thesis describes the determination of the crystal structures of one organo-metallic and three organic compounds. Originally the research programme had envisaged working on substances which were obtained by the corrosive action of hydrocarbon oils on metallic lead, but after some considerable time had been spent on attempting to crystallise these rather intractable materials, the research was switched to deal with other compounds of industrial importance which were more readily available in the Polytechnic. Of the four crystalline compounds investigated, two were connected with the inhibition of the corrosion of steel, one was an additive used in the polymer industry, and one was a molecular complex which had exhibited some unusual physico-chemical properties.